Pemodelan Sistem Pakar untuk Identifikasi Hama Penyakit Tanaman Tebu dengan Metode Dempster-Shafer - Yusuf Nurcahyo; Nurul Hidayat; Rizal Setya Perdana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Every year, the demand for sugar continues to grow as consumption of the community grows and growth in the food and beverage sector. In 2014 the consumption of white crystal sugar (GKP) reaches 2.84 million tons, while in 2015, GKP consumption reached 2.98 million tons and will continue to increase every year. But now the productivity of sugar has decreased. The decline in productivity is caused by several things, one of which is the decrease in the level of sugar content or sugar content in sugarcane stalks. In addition to high rainfall and improper harvesting methods, other sugar cane inhibiting factors are pests and diseases of sugarcane. The limited number of experts and extension agents while in the field, as well as the lack of knowledge of farmers cause problems surrounding pests and diseases of this cane can not be solved immediately. Because of the limitations of these conditions, the authors make an expert system to facilitate the farmers in order to identify diseases and pests in sugar cane plants. This system makes the process of disease identification as well as the conclusion of the diagnosis calculated using the Dempster-shafer method by using fact-insert facts from the user. This expert system makes it easy to determine the type of disease that suits the symptoms. Testing is done by comparing the diagnosis of the system with the results of expert diagnosis using 30 test data consisting of 19 cases of pests and 11 cases of disease in sugarcane.